2017
DOI: 10.1002/mgg3.283
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic findings from clinical whole exome sequencing of diagnostic odyssey patients

Abstract: BackgroundWe characterized the pharmacogenomics (PGx) results received by diagnostic odyssey patients as secondary findings during clinical whole exome sequencing (WES) testing as a part of their care in Mayo Clinic's Individualized Medicine Clinic to determine the potential benefits and limitations to this cohort.Methods WES results on 94 patients included a subset of PGx variants in CYP2C19,CYP2C9, and VKORC1 if identified in the patient. Demographic, phenotypic, and medication usage information was abstract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
(77 reference statements)
1
17
0
Order By: Relevance
“…While most likely unrelated to the clinical indication for sequencing, the test results may nonetheless inform treatment decisions. [37] Furthermore, direct-to-consumer testing may provide an opportunity for patients to order testing on their own [38] and share the test results with providers.…”
Section: Overview Of Pgx Testingmentioning
confidence: 99%
“…While most likely unrelated to the clinical indication for sequencing, the test results may nonetheless inform treatment decisions. [37] Furthermore, direct-to-consumer testing may provide an opportunity for patients to order testing on their own [38] and share the test results with providers.…”
Section: Overview Of Pgx Testingmentioning
confidence: 99%
“…Next generation sequencing (NGS) approaches specifically designed for PGx have shown promising results, with high concordance (91–99%) with conventional PGx methods . Moreover, Cousin et al . have shown that extracting information on three PGx genes from existing clinical WES data can be beneficial in terms of drug dose and response in a small cohort of 94 patients.…”
mentioning
confidence: 99%
“…Next generation sequencing (NGS) approaches specifically designed for PGx have shown promising results, with high concordance (91-99%) with conventional PGx methods. [8][9][10] Moreover, Cousin et al 11 have shown that extracting information on three PGx genes from existing clinical WES data can be beneficial in terms of drug dose and response in a small cohort of 94 patients. However, this study is limited by investigating a small number of PGx genes rather than extracting a full panel of genes with actionable recommendations in PGx guidelines as well as by the use of a limited sample size.…”
mentioning
confidence: 99%
“…In a series of whole exome sequencing results on 94 young patients with a median age of 10 years, a subset of PGx variants in CYP2C19, CYP2C9, and VKORC1 was reported. 3 Most tested patients had dominant neurologic pathology (71%) and were currently taking medications (90%). Of the 94 PGx-evaluated patients, 91% had at least 1 variant allele reported, and 20% had potential immediate implications on current medication use.…”
mentioning
confidence: 99%
“…Of the 94 PGx-evaluated patients, 91% had at least 1 variant allele reported, and 20% had potential immediate implications on current medication use. 3 Therefore, the decision about selecting the patient-appropriate test, with or without components such as PGx or secondary results, should take into account multiple factors, including the indication for testing and the clinical scenario.…”
mentioning
confidence: 99%